PENGARUH PENAMBAHAN SERAT LIMBAH BANNER TERHADAP KUAT LEKAT DAN MIKROSTRUKTUR BETON SERAT PASCA BAKAR SEBAGAI SUPLEMEN BAHAN AJAR MATA KULIAH TEKNOLOGI BETON - Anis Rahmawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The purpose of this study, 1) know how the addition of fiber length variation of banners and combustion temperature variations to bond strength post-burn concrete, 2) know the change of microstructures of concrete by the addition of fiber the waste banner on some variations of the length of the fiber and temperature variations pre and post-burn, 3) know optimum value the addition of fiber waste banner that will produce concrete with bond strength post-burn concrete maximum.This research using quantitative research methods with experimental approach. Variables that affect in this study is 1) free variables include the addition of long fiber waste banner that is 3 cm, 6 cm, 9 cm and in the amount of 0.2% of the weight of the concrete and the temperature variation of combustion that is room temperature (28 ˚ C), 200 ˚ C ˚ C, 300, and 400 ˚ C, 2) variable bound to include bond strength and microstructures of concrete due to variations in the length of the fiber waste banner and combustion temperature variations. Research results as follows 1) addition of long fiber waste banner resulting in a decrease in the temperature of 300 ˚ C and rise at a temperature of 400 ˚ C, 2) change in microstructures of concrete with addition of waste fiber banner on some variations of the length of the fiber and combustion temperature variations can be seen from the pores and cracks in the concrete post-burn that looks more than concrete pre-burn, 3) addition of long fiber waste banner that generates maximum value bond strength the concrete post-burn occurred at the addition of long fiber waste banner 3 cm with combustion temperatures 200 ˚ C.